Hyperacute postprocedural high platelet reactivity: a novel predictor for in-hospital adverse events in acute coronary syndrome with prasugrel loading. (14th October 2021) - Kuroda, K; Tsuji, M; Saito, E; Kawamura, K; Ono, T; Tokioka, K; Kawai, Y
Abstract: Introduction: Postprocedural High platelet reactivity (HPR) seems to associate long term adverse cardiovascular events, mainly intrastent thrombosis. However, the relationship between hyper-acute postprocedural HPR with prasugrel loading and clinical outcomes in acute coronary syndrome (ACS) is still unclear. Moreover, factors contributing HPR in ACS with prasugrel loading are also unknown. Purpose: This study aimed to assess the impact of hyper-acute postprocedural HPR with prasugrel loading on clinical outcomes in ACS during hospitalization, as well as to define appropriate cut-off values and identify contributing factors of HPR. Methods: We performed a single-centre, retrospective observational study that enrolled 207 patients who underwent emergent PCI for ACS with prasugrel loading. The P2Y12reaction unit (PRU) value was measured immediately after PCI with the VerifyNow System. The primary endpoint was major adverse cardiac events (MACE, defined as the composite of death, myocardial infarction, stroke, heart failure, ventricular arrhythmia needing defibrillation). Results: Mean patient age (standard deviation) was 70.5 (±13.0) years, 78.7% were male, and average time from prasugrel intake to PRU calculation was 98.3 (±49.1) min. During a mean hospital stay of 15.9 (±9.3) days, there were 34 in-hospital MACE (16.4%) and 10 deaths (4.8%). Thrombosis events, didn't stand out and mechanical complications, such as cardiac rupture and cardiac tamponade occupies most of cardiovascular death which occurred before 10 days on admission. PRU was significantly higher in MACE group than Non-MACE group (279±65 vs 227±72, p<0.001 respectively). The ROC curve analysis of PRU for discriminating significant in-hospital MACE showed the cut off value of 293 (sensitivity:52.9%, specificity:83.2% [AUC=0.709, p<0.0001]). 47patients (29.4%) were thus categorized as HPR (PRU>293) immediately after emergent PCI. Kaplan-Meyer curve showed MACE events occurred in HPR group than non-HPR group (38.2% vs 10.0%, p<0.001). Multiple cox analysis demonstrated that HPR was independent predictors of MACE in patients with ACS underwent PCI (OR 5.416, 95% CI 2.157–13.598, p<0.0001). Multiple logistic regression model showed female sex, low haemoglobin value, and large mean platelet volume were independent predictors of HPR. Conclusion: PRU was significantly higher in MACE group, and appropriate cut-off value of HPR in this study was 293. HPR was independent predictor of MACE during hospitalization, however thrombosis event was not significant. Evidence of clinical impact with postprocedural HPR within 120 minutes after prasugrel loading is scarce. This study shows post-procedural HPR, even without sufficient time after prasugrel intake, can be a useful predictive marker of adverse events during hospitalization. FUNDunding Acknowledgement: Type of funding sources: None.